(untitled) (Proceedings of Faculty of Civil Engineering, 2019)
A construction project is non-routine, unrepeatable and a unique venture that has separate time, financial and technical achievement goals. Managing a construction project means applying knowledge, skills, and techniques to regulate the course of project activities to achieve project goals. Primarily, this means construction completion within the project contracted deadline and the budget, with satisfactory performance quality. The problem of overruns on the agreed deadline and budget is a global phenomenon, both in developed and developing countries and is therefore often at the center of research interest from various observation aspects. In doing so, various research methods and mathematical data processing tools are used. The aim of this paper is to identify the proportion and causes of overruns in projects and to provide guidelines for their reduction. For the purpose of the research, a multiple case study was used. Data for twelve different projects that were carried out in the Republic of Croatia in 2018 were collected. Data includes technical characteristics of objects, contracted deadlines and costs, performance quality, overrun proportion, and causes of their occurrence. The data were collected by inspecting the documentation and interviewing the manager of each construction site. By data analysis and processing, trends of overruns are identified as well as weak points in planning and managing these project. On that basis, guidelines and recommendations are given to reduce the time and costs overruns in future projects.